Idiopathic acute fatty liver of pregnancy. Issue 10 (October 1970) - Breen, K. J.; Perkins, K. W.; Mistilis, S. P.; Shearman, R.
Abstract : A maternal survivor of idiopathic fatty liver, with the characteristic histological appearance on liver biopsy, is reported. Profound hypoglycaemia was the major complication in this patient and it is suggested that more attention should be given to the blood glucose in this disease. The consideration of future pregnancy in this patient is discussed.